Pertimbangan Hakim dalam Penerapan Hukum Bagi Tindak Pidana Kekerasan yang Dilakukan Secara Bersama-Sama Terhadap Orang di Muka Umum - Etriwan O.S.Lau; Rudepel Petrus Leo; Darius A.Kian (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Criminal acts are behaviors in which a person has violated the provisions of the law and legal norms that apply in the community. One of the most prominent criminal acts today is ganging up. Ganging up is a crime committed by more than one person with the aim of beating or even killing their target. One case of ganging up is a case of violence that occurred in the Kauboke area, Kolhua Village, Maulafa District, Kupang City on Friday, November 13, 2020 at around 19.30 WITA. This study aims to analyze how the law is applied to violent crimes in decision Number 214 / pid.B / 2021 / PN.Kpg and the judge's considerations in imposing sanctions on the perpetrators in the decision of case Number 214 / Pid.B / 2021 / PN.Kpg. This research is an empirical legal research where the data used is obtained directly from the research location. This study uses interview guidelines with one informant, the data in this study is analyzed descriptively-qualitatively. The results of the study show: (1) The application of law and criminalization to the case with decision Number 214/Pid.B/2021/PN.Kpg has been carried out correctly. (2) The judge's considerations in imposing a sentence have been carried out correctly. The judge makes a decision by carefully considering various factors by looking at the various impacts on the victim and the defendant.